Unravelling mass transport in hierarchically porous catalysts. Issue 19 (24th April 2019) - Isaacs, Mark A.; Robinson, Neil; Barbero, Brunella; Durndell, Lee J.; Manayil, Jinesh C.; Parlett, Christopher M. A.; D'Agostino, Carmine; Wilson, Karen; Lee, Adam F.
Abstract : Hierarchical porous catalysts offer highly connected architectures for enhanced transport of bulky molecules and the sustainable manufacturing of bio-derived platform chemicals and fuels. Abstract : Bio-derived platform chemicals and fuels are important for the development of sustainable manufacturing. However, their efficient production from biomass necessitates new catalysts and processes optimised for the selective transformation of large molecules. Mesoporous and hierarchically porous functional materials are promising catalyst candidates for biomass valorisation, but quantitative relationships between pore dimensions/connectivity, mass transport, and corresponding catalytic performance are poorly defined. A family of hierarchical macroporous–mesoporous SBA-15 sulfonic acids were prepared with tunable macropore diameters for carboxylic acid esterification. Turnover frequencies for long-chain (palmitic and erucic) acids were proportional to macropore diameter (≤370 nm), whereas propanoic acid esterification was independent of macropore size. Pulsed field gradient NMR diffusion experiments reveal that larger macropores enhance esterification of bulky carboxylic acids by conferring superior pore interconnectivity and associated mass transport.